Metabolomics and Sensory Evaluation Reveal the Aroma and Taste Profile of Northern Guangdong Black Tea - Jialin Chen; Binghong Liu; Yide Zhou; Jiahao Chen; Yanchun Zheng; Hui Meng; Xindong Tan; Peng Zheng; Binmei Sun; Hongbo Zhao; Shaoqun Liu (Foods, 2025)
The sensory quality of black tea is intrinsically linked to cultivar genetics, yet comprehensive characterization of flavor compounds in emerging northern Guangdong black tea (NGBT) remains limited. This study employed high-performance liquid chromatography-ultraviolet (HPLC-UV) and headspace solid-phase microextraction coupled with GC-MS (HS-SPME-GC-MS) to analyze non-volatile and volatile compounds in five NGBT cultivars—Jinshahong (JSH), Danxia No.1 (DXY), Danxia No.2 (DXE), Yingde Black Tea (QTZ), and Yinghong No.9 (YHJ)—alongside sensory evaluation. Orthogonal partial least squares-discriminant analysis (OPLS-DA) identified key non-volatile discriminants (VIP > 1) ranked by contribution: total catechins > simple catechins > CG > EGCG > ester catechins > EGC. HS-SPME-GC-MS detected 97 volatiles, with eight aroma-active compounds exhibiting OAV > 1 and VIP > 1: Geraniol > Methyl salicylate > Linalool > β-Myrcene > Benzyl alcohol > (Z)-Linalool Oxide > Phenethyl alcohol > (Z)-Jasmone. These compounds drive cultivar-specific aromas in NGBTs. Findings establish a theoretical framework for evaluating cultivar-driven flavor quality and provide novel insights for targeted breeding and processing optimization of NGBTs.